Balantidiosis - Céspedes, Rodolfo (1955)
Nine cases of human balantidiasis are presented, six of them located in the appendix, three appearing as active acute colitis. The colitis forms were violently acute and had a rapid fatal issue, with perforation of the colon wall and peritonitis in two cases. The appendicular cases evolved slowly, always with the antecedent of abdominal pain predominantly on the right iliac fossa. Only one of the appendicular cases showed perforation and caused a periappendicular abscess. None of the appendicular cases was fatal, although one had a very difficult post-operative picture. In two of the cases of colitis and one of the cases of appendicitis, balantidiasis was associated with trichocephalosis. When no bacterial complication exists, Balantidium Iesions are characterized by ulcers affecting the mucosa and submucosa and are predominantly hemorrhagic. In one fatal case trophozoites of B. coli found within one vein in the submucosa. No hepatic lesions were found in any of the cases. Of the nine cases eight a came from rural areas, one from an urban zone. There is on record also case of a carrier of B. coli. The low íncidence of human balantidiasis in this area is stressed.